Lepers Living Experiences - Yanli Everson Tuwohingide; Kumboyono Kumboyono; Yulian Wiji Utami (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Leprosy is an infectious disease that causes problems from a medical perspective to social, economic, cultural, security and health problems. Leprosy is generally found in developing countries as a result of the country's limited ability to provide adequate services in the health sector. This study aims to explore the life experiences of leprosy sufferers on the island of Mahangetang by using a phenomenological approach. The data was collected using the purposive sampling technique, through field observations and in-depth interviews with 7 participants. Data analysis was carried out using thematic analysis methods. The results of the study found eight themes, namely, activities carried out by people with leprosy, economic conditions that occurred while suffering from leprosy, psychological burden while suffering from leprosy, behavior seeking treatment, the meaning of leprosy, social support and illness experienced as destiny that must be accepted. The conclusion of this study based on the results of interview analysis found 8 themes, 20 sub-themes and 41 categories. Although suffering from leprosy, all activities are still carried out, both work and religious activities, even though the psychological burden is directly experienced by leprosy sufferers, but with social support, it can strengthen the psychology of leprosy patients so that they remain patient in undergoing treatment. Abstrak: Penyakit kusta merupakan salah satu penyakit menular yang menimbulkan masalah dari segi medis sampai masalah sosial, ekonomi, budaya dan keamanan. Penyakit kusta pada umumnya terdapat di negara yang sedang berkembang sebagai akibat keterbatasan kemampuan negara tesebut dalam memberikan pelayanan yang memadai dalam bidang kesehatan. Penelitian ini bertujuan mengeksplorasikan pengalaman hidup penderita kusta di pulau Mahangetang dengan menggunakan pendekatan fenomenologi. Pengumpulan data dilakukan dengan teknik Purposive Sampling, melalui observasi lapangan dan proses wawancara mendalam kepada 7 partisipan. Analisis data dilakukan menggunakan metode analisis tematik. Hasil penelitian menemukan delapan tema yaitu, kegiatan yang dilakukan penderita kusta, Kondisi ekonomi yang terjadi selama menderita kusta, Beban psikologi selama menderita kusta, perilaku mencari pengobatan, Makna penyakit kusta, Dukungan sosial dan Penyakit yang dialami sebagai takdir yang harus diterima. Kesimpulan dari penelitian ini berdasarkan hasil analisis wawancara menemukan 8 tema, 20 sub tema dan 41 ktaegori. Walaupun menderita kusta semua aktivitas tetap dijalani baik itu pekerjaan maupun kegiatan keagamaan, meskipun beban psikologi secara langsung dialami oleh penderita kusta, namun dengan adanya dukungan sosial dapat menguatkan psikologi penderita kusta sehingga tetap sabar dalam menjalani pengobatan.